2020
DOI: 10.1101/2020.06.08.140087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantifying the contribution of Neanderthal introgression to the heritability of complex traits

Abstract: 11 12 Background: Nearly all Eurasians have ~2% Neanderthal ancestry due to several events of 13 inbreeding between anatomically modern humans and archaic hominins. Previous studies 14 characterizing the legacy of Neanderthal ancestry in modern Eurasians have identified 15 examples of both adaptive and deleterious effects of admixture. However, we lack a 16 comprehensive understanding of the genome-wide influence of Neanderthal introgression on 17 modern human diseases and traits. 18 Results: We integrate rece… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 78 publications
4
16
1
Order By: Relevance
“…Large-scale sequencing efforts, in combination with analysis of clinical biobanks and improved computational methods, have revealed the potential impacts of introgressed DNA on modern human genomes. Several recent studies link regions of archaic admixture in modern populations with a range of diseases, including immunological, neuropsychiatric and dermatological phenotypes 102 , 132 139 . This demonstrates the functional impact of introgressed sequence on disease risk in non-African humans today.…”
Section: Recent Human Demographic Historymentioning
confidence: 99%
“…Large-scale sequencing efforts, in combination with analysis of clinical biobanks and improved computational methods, have revealed the potential impacts of introgressed DNA on modern human genomes. Several recent studies link regions of archaic admixture in modern populations with a range of diseases, including immunological, neuropsychiatric and dermatological phenotypes 102 , 132 139 . This demonstrates the functional impact of introgressed sequence on disease risk in non-African humans today.…”
Section: Recent Human Demographic Historymentioning
confidence: 99%
“…Based on the fossil record previous studies presented evidence for differences in skeletal features and fat distribution between Neandertals and modern humans [56]. Furthermore, it has repeatedly been shown that introgressed Neandertal DNA significantly influences skin and hair traits [5][6][7]. Some of these studies have also demonstrated that Neandertal DNA showed an over-proportional number of associations with behavioral traits such as sleep [5][6][7]57], which are partially controlled by hormones produced in the thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used information from genome-wide association studies to link archaic DNA to their potential phenotypic effects. These studies have shown that Neandertal DNA significantly influences skin and hair traits, immunity and behavioral phenotypes [5][6][7][8]. Many of the phenotype-associated archaic variants have been associated with regulatory effects as well, including several instances of Neandertal DNA with additional evidence for local adaptation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have used large genotypic data sets with phenotypic data, such as electronic health records to link archaic alleles with specific traits, and have identified Neanderthal alleles associated with traits including neurological phenotypes, height, blood coagulation and inflammation, chronotype, and skin and hair pigmentation ( Simonti et al 2016 ; Dannemann and Kelso 2017 ; Prüfer et al 2017 ). More recently, ( McArthur et al 2020 ) used an approach based on associating genome-wide trait heritability with Neanderthal ancestry to identify impacts of Neanderthal introgression on hair and skin, autoimmunity, chronotype, bone density, lung capacity, and menopause age. Although many associations between archaic alleles and phenotypes have been discovered, recent re-analysis has found that many of these associations are actually due to nonarchaic variants in linkage with archaic haplotypes ( Skov et al 2020 ).…”
Section: Functional Consequences Of Archaic Introgressionmentioning
confidence: 99%